Davos man : how the billionaires devoured the world - Goodman, Peter S. (Custom House, 2022)
"From the New York Times's Global Economics Correspondent, a masterwork of reporting and explanatory journalism that exposes how billionaires' systematic plunder of the world has transformed 21st century life and dangerously destabilized democracy"--